Emotions analysis in public spaces for urban planning. (August 2021) - Kaklauskas, A.; Bardauskiene, D.; Cerkauskiene, R.; Ubarte, I.; Raslanas, S.; Radvile, E.; Kaklauskaite, U.; Kaklauskiene, L.
Abstract: Scientists have been attempting to apply emotions in the urban planning process with qualitative methods (surveys, interviews, questionnaires and the like) since the mid-1900s. However, at that time, there were no possibilities for applying biometric or other kinds of tracking and remote technologies to detect and recognize the emotions felt by other people. The 21st century brought forth such opportunities. Nonetheless, even currently, the remotely integrated, emotional, affective and physiological states, arousal and valence (MAPS) of individuals residing or visiting urban areas are very seldom analysed. Meanwhile stakeholder groups are unable to receive digital advice with a goal to upgrade urban areas to be more pleasant, comfortable and sustainable. In such a context, the authors of this study developed an Affective System for Researching Emotions in Public Spaces for Urban Planning (ASP System). This System has added to the body of knowledge on research in several ways. ASP can prove a helpful supplement to urban planning and public participation practice by gathering and analysing MAPS data of passersby, weather conditions, pollution and other data. This unique combination of MAPS data can assist city stakeholders in initiating effective planning solutions based on an inhabitant-centric method. Additionally ASP employs a neuro decision matrix, which assisted in deriving a comprehensive analysis of the urban areas under deliberation by MAPS parameters. This article also submits eight avenues of practical use for urban planners when employing MAPS data and the ASP Method and System. The case studies on cultural heritage sustainability confirm the accuracy of the developed ASP Method and System. Highlights: ASP studies emotional, affective, and physiological states, arousal and valence (MAPS) of the passersby. Human MAPS, built environment, and pollution are all interrelated, and stakeholders can use it in city planning. ASP creates digital affective, emotional, and physiological maps of public spaces (PS) and delivers tips. ASP calculates the hedonic, customer-perceived, hedonic-market, and hedonic-investment values. ASP compiles many alternative urban planning texts and selects the more appropriate ones.